Meningkatkan Keputusan Pembelian Konsumen The Body Shop Melalui Green Marketing dan E-Wom Dimediasi Kepuasan Konsumen: ( Studi Kasus Pelanggan di Sumarecon Mall Serpong) - Siti Asriah Immawati; Rosyid, Rosyid; Kerin Paramita (MAMEN: Jurnal Manajemen, 2023)
The purpose of this study was to determine how to improve purchasing decisions that are influenced by green marketing and eWom mediated by consumer satisfaction with The Body Shop products. This study uses a quantitative approach with an associative approach. This study consists of two independent variables, namely green marketing and eWom, one moderating variable, namely customer satisfaction and one dependent variable, namely purchasing decisions. The sample in this study amounted to 96 consumers of The Body Shop Sumarecon Serpong in the period January to April 2023.The sampling technique used was accidental technique. The data source was obtained through a questionnaire of 18 statements using a Likert scale of 1 (one) to 7 (seven) distributed via google form. The data analysis technique used is multiple linear regression with the help of SmartPLS software. From the results of the analysis, it is found that Green marketing has a positive and significant effect on customer satisfaction, eWom has a positive and significant effect on customer satisfaction, Green marketing has a positive and significant effect on purchasing decisions. eWom has a positive and insignificant effect on purchasing decisions. Customer satisfaction has a positive and insignificant effect on purchasing decisions.